Bioavailability of heavy metals as a consequence of the variation in the contraction of humic and fulvic acids in the sediment of the Collotacocha high Andean wetland (SCIÉNDO INGENIUM, 2022)
The objective was to determine the bioavailability of heavy metals as a consequence of the variation in the contraction of humic and fulvic acids in the sediment of the Collotacocha high Andean wetland, by determining the concentration ratio of organic acids (humic and fulvic) as a function of the variation of pH of the sediment in the wetland and the determination of the metals in the exchangeable and easily reducible fractions of the Tessier sequential extraction speciation. Eight sampling stations were carried out, where the percentage ratio of organic acids, the content of aluminium, arsenic, iron and lead, in the different fractions of the Tessier sequential extraction, were determined by means of UV-Visible spectroscopy. The results show that in the organic acids there is a higher concentration of humic acids in relation to the fulvic acids, in the sequential extraction it was determined that the bio-availability of heavy metals was: Al 27.3%, As 28.0%, Fe 26.3% and Pb 20.9% (higher values). It is concluded that there is a higher concentration of humic acids with respect to fulvic acids when the pH of the sediment is acidic and the bioavailability of heavy metals decreases in the sediment of the wetland.
Keywords: phytoremediation; pollution; sedimentation; chelating activity; chemical extraction